Influence of Workload and Quality of Work Life on Employee Performance with Competency Mediation - Septi Suryani; Muryati (Optima Science, 2025)
This research aims to determine the effects of workload and Quality of Work Life Regarding Employee Performance Mediated by Competence in Employees of the Bromo Tengger Semeru National Park Center. The research was conducted on civil servants at the Bromo Tengger Semeru National Park Center. The population in this study were all civil servants who worked at the Bromo Tengger Semeru National Park Hall. The sampling technique used in this research is Probability Sampling with a total of 72 respondents. And the data is processed through software Smart Partial Least Square (PLS). The results of the data analysis that has been carried out can be concluded as follows: (1) Workload has no effect on employee performance, (2) Quality Of Work Life has a positive influence on employee performance, (3) workload has no effect on competency, (4) Quality Of Work Life able to encourage increased competence. (5) Strong competency has an effect on better employee performance. (6) Workload does not have a significant effect on employee performance and competency. (7) Quality of Work Life (QWL) plays an important role in encouraging increased employee performance, with competence as a mediator.